The galactic goal - Stilton, Geronimo (Stilton, Geronimo. Spacemice, 2015)
"The spacemice have received an invitation to participate in the intergalactic soccerix championship. It's a tournament for the most popular sport in space! But Geronimo doesn't even know how to play Soccerix, let alone lead a team to victory against aliens with bizarre skills (like flying)! Can the spacemice team prevail?"--Page 4 of cover.